2022
DOI: 10.15212/amm-2022-0006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a cytisine-based EED-EZH2 protein-protein interaction inhibitor preventing metastasis in triple-negative breast cancer cells

Abstract: Enhancer of zeste homolog 2 (EZH2) is activated in breast cancer, particularly in triple-negative breast cancer (TNBC), and is critical for cell invasion. It interacts with embryonic ectoderm development (EED) in maintaining cancer stem cells (CSC) and epithelial-mesenchymal transition (EMT) properties, hence promoting CSC metastasis. Because the association of EZH2 with EED promotes the catalytic activity of EZH2, inhibiting the EED-EZH2 interaction is a potential therapeutic strategy for treating EZH2-depend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Malignant tumor cells acquire abnormal movement to intrude into the surrounding tissue parenchyma 46 . Polarized cellular response allows cancer cells to move forward and up the chemoattractant gradient, which is an effective motility of multiple tumor cells 47 , 48 . Arf6 regulates polarized morphology, endocytic trafficking and actin remodeling of cells.…”
Section: Roles and Mechanisms Of Arf6mentioning
confidence: 99%
“…Malignant tumor cells acquire abnormal movement to intrude into the surrounding tissue parenchyma 46 . Polarized cellular response allows cancer cells to move forward and up the chemoattractant gradient, which is an effective motility of multiple tumor cells 47 , 48 . Arf6 regulates polarized morphology, endocytic trafficking and actin remodeling of cells.…”
Section: Roles and Mechanisms Of Arf6mentioning
confidence: 99%
“…Natural products are one of the major sources in drug discovery due to their diverse chemical scaffolds and activity profiles (Fang et al, 2020;Yang et al, 2020;Yang et al, 2021a;Cheng et al, 2022b;Song et al, 2022). Many natural products and their derivatives have been found with in vitro inhibitory activity against LSD1.…”
Section: Natural Productsmentioning
confidence: 99%
“…Targeting the protein-protein interaction (PPI) is also an effective method to improve the selectivity of enzymes (Yang et al, 2018a;Cheng et al, 2020;Yang et al, 2021a;Yang et al, 2021c;Yang et al, 2021d;Yang et al, 2022), blocking the interaction between LSD1 and its client proteins may be also a useful strategy to develop selective LSD1 inhibitors. Metal complexes have showed promising in vivo activity for BC treatment (Yang et al, 2018b;Cheng et al, 2022b), andYang et al (2017) have also identified a rhodiumbased LSD1 inhibitor with in cellulo anticancer activity against prostate cancer, which suggested this kind of compound is a unique source for the discovery of potent and selective LSD1 inhibitors against BC treatment. Several drug design strategy such as computer aided drug optimization and proteolysis targeting chimera (PROTAC)-strategy have been introduced to discover lead compounds against LSD1 with better biocompatibility and in vivo potency (Liu et al, 2020b;Martín-Acosta and Xiao, 2021).…”
Section: Dual-target Inhibitors and Combined Therapymentioning
confidence: 99%
“…Molecular docking has been one of the most commonly used types of structure-based drug design since the development of the first algorithms in the 1980s. Our group has discovered several protein-protein interaction inhibitors through in silico virtual screening, including CDK9-cyclin T1 protein-protein interaction inhibitors [20,21], EED-EZH2 protein-protein interaction inhibitors [22], and Keap1-Nrf2 protein-protein interaction inhibitors [23].…”
Section: Introductionmentioning
confidence: 99%